ANALISIS PENGARUH KUALITAS PELAYANAN, HARGA DAN IKLAN TERHADAP KEPUTUSAN KONSUMEN DALAM MENGGUNAKAN JASA LOGISTIK JNE (STUDI KASUS CV.CIPTA ABDI MANDIRI DI DAERAH CENGKARENG) - Alant Junedi (Universitas Mercu Buana, 2014)
Abstract. This study aims to analyze and empirically test the hypotheses of theeffect of service quality, price and advertising on customers decision in usingJNE’s logistic service (case study CV. Cipta Abdi Mandiri at Cengkareng area).Sample of respondents in this study are customer of CV. Cipta Abdi Mandiri wasselected randomly at period 15 July until 31 August 2014 about 100 persons.Multiple Regression Linear used to analyze and test the hypotheses. The studyfound that model were proposed is fit based on Goodness of Fit Indices.Hypotheses testing concludes that service quality and price have significants andpositive effect on costumers decision of CV. Cipta Abdi Mandiri whileadvertising have no significant effect.Keywords: Service Quality, Price, Advertising, Costumers Decision